USIA Foreign Service personnel system : hearing before the Ad Hoc Subcommittee on a Foreign Service Information Officer Corps of the Committee on Foreign Relations, United States Senate, Ninetieth Congress, first session, on S. 633 and S. 2002, bills to promote the foreign policy of the United States by strengthening and improving the foreign service personnel system of the U.S. information agency through establishment of a foreign service information officer corps, September 28, 1967. (1967)
Summary goes here